Positive behaviour support through the learning environment diagnostic survey: A socio-legal preventive model for addressing student violence and bullying - Syaifudin, Syaifudin; Afriadi, Bambang (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to develop and test an integrative model of Positive Behaviour Support (PBS) grounded in the Learning Environment Diagnostic Survey (LEDS) as a preventive framework for student violence and bullying within a socio-legal context. Employing a mixed-methods design, the research combined a quantitative survey of 250 students with qualitative, in-depth interviews involving 20 key stakeholders. The findings demonstrate the model's effectiveness, showing a significant reduction in violent behavior (mean score decrease from 3.21 to 2.18, p < 0.05) and a substantial increase in prosocial behavior (mean score rise from 3.45 to 4.12, p < 0.01). Qualitative data further supported these results, indicating improved student cooperation and reduced verbal harassment. The conclusion is that the PBS–LEDS model successfully bridges data-driven diagnosis with behavioral intervention, aligning with national legal frameworks like Law No. 35/2014 and Ministerial Regulation No. 46/2023. As such, it has significant practical implications for both educational practice and public policy, providing schools with a strategic tool to fulfill their legal obligations in safeguarding children.